The level of awareness about eating disorder among bachelor degree students from Faculty of Hotel and Tourism Management of UiTM Terengganu Kampus Dungun / Kamal Ikhwan Kamal Razman & Muhd Fithri Senin - Kamal Razman, Kamal Ikhwan; Senin, Muhd Fithri (2018)
Awareness about eating disorder is somehow lacking among the adolescents group nowadays. This study aimed to determine the level of awareness about eating disorders among Bachelor Degree students from Faculty of Hotel and Tourism Management of UiTM Cawangan Terengganu. A questionnaire that contains Eating Disorder Awareness Test (EDAT) has been distributed online to 144 respondents. The result shows that the respondents is truly aware about Eating Disorder. This study concludes that it might be because of the knowledge level of the respondents that are currently enrolling in the food related course. Despite that, this research can be improved by modifying the number of samples, locations and knowledge level of the respondents.